A meta-analysis of risk factors for a Dacron-cuffed catheter related infection in hemodialysis - Wen Chen; Zaoju Wang; Guoping Wang; Chunyu Cao; Bo Hong; Jinying Liu; Fuhua Xie; Runxiu Wang (BMC Nephrology, 2024)
Abstract Objective To provide theoretical basis for prevention of a Dacron-cuffed catheter related infection (CRI), the risk factors of CRI in hemodialysis patients were systematically evaluated. Methods Eight databases, including PubMed, Cochrane library, EMBASE, Web of Science, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Database (CBM), Wanfang Database and Chinese Scientific Journal Database (VIP), were searched to screen out literatures related to the risk factors of long-term indwelling a Dacron-cuffed CRI in hemodialysis. Meta-analysis of risk factors for a Dacron-cuffed CRI in hemodialysis and publication bias test were performed using RevMan 5.4 software. Results After screening, 13 literatures involving a Dacron-cuffed CRI were included, with a total of 625 patients, and the infection rate was 11.7%. The combined OR value and 95% confidence interval (CI) of all factors were: Combined with Diabetes (1.94, 1.51 ~ 2.50), Hb (1.82, 1.35 ~ 2.44), age (2.38, 1.06 ~ 5.34), catheter indwelling time (1.79, 1.21 ~ 2.66), serum albumin (2.26, 1.25 ~ 4.08), catheter indwelling site (3.29, 1.74 ~ 6.23) and the number of tube placement (5.40, 2.65 ~ 11.02). Conclusions The main risk factors for a Dacron-cuffed CRI in hemodialysis were combined with diabetes, hemoglobin level, age, catheter indwelling time, serum albumin level, femoral vein catheter indwelling and catheterization times. In other words, hemodialysis patients are at higher risk of CRI if they have diabetes, or if they have a lower hemoglobin level, or if they are older, or if they have a longer duration of catheterization, or if they have a lower serum albumin level, or if they have a femoral vein catheter, or if they have more catheters.